Clemastine Rescues Chemotherapy-Induced Cognitive Impairment by Improving White Matter Integrity. (21st February 2022) - Chen, Yingxi; Sheng, Jie; Tang, Xiuying; Zhao, Yuhong; Zhu, Shujuan; Liu, Qian
Highlights: Chemotherapy damages cognitive function by injuring white matter integrity. Clemastine can rescue chemotherapy-induced cognitive impairment of mice. Clemastine has ability of rescuing white matter injury induced by chemotherapy. Abstract: With the improvement of cancer treatment techniques, increasing attention has been given to chemotherapy-induced cognitive impairment through white matter injury. Clemastine fumarate has been shown to enhance white matter integrity in cuprizone- or hypoxia-induced demyelination mouse models. However, whether clemastine can be beneficial for reversing chemotherapy-induced cognitive impairment remains unexplored. In this study, the mice received oral administration of clemastine after chemotherapy. The open-field test and Morris water maze test were used to evaluate their anxiety, locomotor activity and cognitive function. Luxol Fast Blue staining and transmission electron microscopy were used to detect the morphological damage to the myelin. Demyelination and damage to the mature oligodendrocytes and axons were observed by immunofluorescence and western blotting. Clemastine significantly improved their cognitive function and ameliorated white matter injury in the chemotherapy-treated mice. Clemastine enhanced myelination, promoted oligodendrocyte precursor cell differentiation and increased the neurofilament 200 protein levels in the corpus callosum and hippocampus. We concluded that clemastine rescues cognitive function damage caused by chemotherapy through improving white matter integrity. Remyelination, oligodendrocyte differentiation and the increase of neurofilament protein promoted by clemastine are potential strategies for reversing the cognitive dysfunction caused by chemotherapy.